Analyzing solitary wave solutions of the nonlinear Murray equation for blood flow in vessels with non-uniform wall properties - İnç, Mustafa; Hussain, Shabbir; Ali, Ali Hasan; Iqbal, Muhammad Sajid; Ashraf, Romana; Tarar, Muhammad Akhtar; Adnan, Muhammad (Nature Portfolio, 2024)
Solitary wave solutions are of great interest to bio-mathematicians and other scientists because they provide a basic description of nonlinear phenomena with many practical applications. They provide a strong foundation for the development of novel biological and medical models and therapies because of their remarkable behavior and persistence. They have the potential to improve our comprehension of intricate biological systems and help us create novel therapeutic approaches, which is something that researchers are actively investigating. In this study, solitary wave solutions of the nonlinear Murray equation will be discovered using a modified extended direct algebraic method. These solutions represent a uniform variation in blood vessel shape and diameter that can be used to stimulate blood flow in patients with cardiovascular disease. These solutions are newly in the literature, and give researchers an important tool for grasping complex biological systems. To see how the solitary wave solutions behave, graphs are displayed using Matlab.
Keywords: Solitary wave solutions; Nonlinear Murray equation; Modified extended direct algebraic method